2016
DOI: 10.6061/clinics/2016(10)09
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric minor head trauma: do cranial CT scans change the therapeutic approach?

Abstract: OBJECTIVES:1) To verify clinical signs correlated with appropriate cranial computed tomography scan indications and changes in the therapeutic approach in pediatric minor head trauma scenarios. 2) To estimate the radiation exposure of computed tomography scans with low dose protocols in the context of trauma and the additional associated risk.METHODS:Investigators reviewed the medical records of all children with minor head trauma, which was defined as a Glasgow coma scale ≥13 at the time of admission to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
4
14
0
1
Order By: Relevance
“…Although self-level falling is not considered a serious trauma mechanism, in the study by Andrade et al, 30% of the patients who had undergone CCT scans comprised patients falling at their own level, and 7.9% of them had abnormal imaging findings [8]. In the study of Klassen et al, only 5 (1.7%) of 296 patients admitted due to falling from a height of b90 cm (including those falling from their own level).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although self-level falling is not considered a serious trauma mechanism, in the study by Andrade et al, 30% of the patients who had undergone CCT scans comprised patients falling at their own level, and 7.9% of them had abnormal imaging findings [8]. In the study of Klassen et al, only 5 (1.7%) of 296 patients admitted due to falling from a height of b90 cm (including those falling from their own level).…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary questions asked in the anamnesis of a trauma patient admitted to the emergency department is the mechanism of trauma. The mechanism of trauma may sometimes be an indication for imaging alone [6,8]. Many studies have reported that the most common mechanism of trauma in children is falling (70% in Powel et al, 81% in Andrade et al, 47% in Klassen et al, and 52.6% in Alharthy et al) [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When such patients are subjected to repeated CT examination, there is an iatrogenic risk of inducing repeated low dose radiation, which may result in cancers in adult life. 15…”
Section: Discussionmentioning
confidence: 99%
“…[17], natomiast ma potwierdzenie w danych przedstawionych przez Andrade i wsp. [22]. Wymioty po lekkim urazie głowy notowano u 35% dzieci.…”
Section: Dyskusjaunclassified